Financial system stability in Indonesia and its relationship with economic growth before and during the Covid-19 pandemic - Siswantoro, Siswantoro (Asian Management and Business Review, 2024)
The purpose of this study is to assess the condition of financial system stability in Indonesia both before and during the Covid-19 pandemic and to look at its relationship with economic growth. This study develops six sub-sector groups described in 19 indicators in order to assess the condition of the financial system. Quarterly data for 6.5 years from Quarter I 2016 to Quarter II 2022 was evaluated. To assess the condition of the financial system, this study uses a composite index approach with the normalized max-min method. The correlation analysis method is used to assess the relationship between the index of financial system conditions and economic growth. The results showed that during the pandemic, there was a more significant increase in pressure on financial conditions than before the pandemic. The financial system instability index during the pandemic in the second quarter of 2020 was 3 times higher than the average and more than 5 times higher than the same quarter in 2019. In addition, the relationship between the financial condition index and economic growth is at 0.77 (strong category). The implication is this research can provide insight to the government, financial institutions, and the public regarding the condition of financial system stability before and during the Covid-19 pandemic. This research suggests that the government should control credit restructuring policies during the pandemic and strengthen financial institutions. This research has limitations in terms of objects that only include conventional financial institutions. Further studies can use other objects such as Islamic financial institutions.